SOEs under the Soeharto’s New Order Regime and Reformasi Era - Teuku Syahrul Ansari, Budi Santoso, Paramitha Prananingtyas, Darminto Hartono, Herdi Sahrasad, and Arif Zainudin (International Journal of Advanced Science and Technology, 2020)
Research aims to understand, report, and evaluated  performances of SOEs (BUMN)  in the era of Soeharto New Order and Reformasi post Soeharto, in connection with political-economy dynamics with Literature Review Method. State-Owned Enterprises (SOEs or BUMN) reform policy in Indonesia that optimally aligns the company's internal policies and industrial policies, and optimizes the principles of good corporate governance as a whole in order SOE revitalization, bring results and progress.  However, when compared to the performance of similar private businesses, even more so with companies owned by other state governments, SOEs in Indonesia still need a lot of improvement in order to catch up. This research found if the performance of SOEs the greater the role that can be carried out both depends on their leader. For this reason, we coclude that they have to five important points that must be present in the future figure of SOE.